Multidimensional Spot of Domination and Courage Among New Athletes Towards a Coaching Program - 何攀攀 (Pacific International Journal, 2024)
In the realm of competitive sports, athletes face a complex landscape that extends beyond physical demands. The dynamics of athlete-coach relationships, peer interactions, and societal expectations shape their experiences, especially for new athletes. This study delves into the intricate interplay between two fundamental constructs: domination and courage in the context of coaching programs. Domination in sports manifests through coach-athlete power dynamics, peer pressure, and societal expectations. Coaches wield significant influence, impacting athletes’ autonomy and decision-making. Peer interactions exert unspoken pressures to conform to team norms, while external societal expectations, such as academic success and career prospects, add further complexity to athletes’ pursuits. Courage emerges as a critical attribute, enabling athletes to confront challenges, embrace uncertainties, and persevere in adversity. Athletes exhibit courage by asserting individuality, challenging established norms, and demonstrating resilience. This courage serves as a mechanism for resilience and empowerment, allowing athletes to navigate and transcend domination. Holistic athlete development is emphasized, extending beyond physical training to encompass mental and emotional empowerment. Coaching programs should create supportive and empowering environments, prioritizing athlete autonomy, mental resilience, and well-being. This study provides valuable insights into the experiences of new athletes, highlighting the pivotal role of courage in mitigating domination and fostering comprehensive athlete development.